Modeling and docking studies in barley - SOMYA SHARMA; VIJENDRA K. SHARMA (International Journal of Pharma and Bio Sciences, 2018)
Barley is a major cereal crop from Poaceae family grown worldwide and it is one of the first cultivated grains. A number of biotic and abiotic factors affect the crop yield and quality. Among the biotic factors, barley is susceptible to various diseases Common ones are net blotch (caused by Drechslera teres), scald (caused by Rhynchosporium secalis), leaf rust (caused by Puccinia hordei) and powdery mildew (caused by Blumeria graminis f.sp. hordei). Fungal attack is one of the most prevailing concerns for crop and yield loss. B. graminis affects the barley as it causes powdery mildew disease. Barley has its own immunity but that is not sufficiently effective. Therefore, biologists are continuously working towards the plant immunity and control of diseases. Mildew Locus Allele (MLA6) is triggering immunity against the barley powdery mildew fungus and MLA6 interact with MYB6 antagonistically acting transcription factor and their cluster provides immunity against B. graminis to the barley. Recently, adopting new strategies of bioinformatics for designing of molecular model based on the concept of basic local alignment and docking approach for protein-protein interactions is used to generate the 3D model of MLA6and MYB6 through BLASTP and Easy Modeller 4.0. Pathogenesis Related protein (PR5) of barley has anti-fungal properties which releases in result of virulence factor Candidate for Secreted Effect or Proteins (CSEP0064) of B. graminis. Various CSEPs are released during and after haustoria formation in barley. PR5 and CSEP0064 molecular interaction gives insight in the immunity of barley.